2015
DOI: 10.1053/j.gastro.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Derived Growth Factor Receptor-α Regulates Proliferation of Gastrointestinal Stromal Tumor Cells With Mutations in KIT by Stabilizing ETV1

Abstract: Background & Aims In gastrointestinal muscles, KIT is predominantly expressed by interstitial cells of Cajal (ICC) and PDGFRA is expressed by so-called fibroblast-like cells. KIT and PDGFRA have been reported to be co-expressed in ICC precursors and gastrointestinal stromal tumors (GISTs), which originate from the ICC lineage. PDGFRA signaling has been proposed to stimulate growth of GISTs that express mutant KIT, but the effects and mechanisms of selective blockade of PDGFRA are unclear. We investigated wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 33 publications
2
64
0
1
Order By: Relevance
“…The cooperative oncogenic effects of ETV1 with KIT-or BRAF-activating mutations is in part through ETV1 protein stabilization. Therefore, MAPK pathway inhibition with either KIT or MEK inhibitors leads to rapid ETV1 degradation (15)(16)(17). This implicates the dynamic regulation of ETV1 protein stability as a critical mechanism to couple ERK activity to a downstream nuclear transcriptional response in GISTs and melanoma.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The cooperative oncogenic effects of ETV1 with KIT-or BRAF-activating mutations is in part through ETV1 protein stabilization. Therefore, MAPK pathway inhibition with either KIT or MEK inhibitors leads to rapid ETV1 degradation (15)(16)(17). This implicates the dynamic regulation of ETV1 protein stability as a critical mechanism to couple ERK activity to a downstream nuclear transcriptional response in GISTs and melanoma.…”
Section: Introductionmentioning
confidence: 98%
“…In GISTs, the ETS factor ETV1 is a lineage-specific master regulator that cooperates with KIT-and PDGFRA-activating mutations in pathogenesis (15)(16)(17)(18)(19). In cutaneous melanoma, ETV1 is recurrently amplified and cooperates with the BRAF V600E -activating mutation in oncogenesis (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…1 ICCs play a central role in gastrointestinal motility by generating electrical slow waves underlying phasic contractile activity, mediating nerve-muscle interactions and by setting smooth muscle membrane potential and tone. 1,2 ICCs differentiate from embryonic 3 and adult stem cells (ICC-SCs) 4,5 in response to the interdependent actions of the ets family transcription factor ETV1, a master regulator of ICC fate, 68 and KIT ligand (KITL, also known as stem cell factor) signaling via the receptor tyrosine kinase KIT. 3,9 …”
Section: Introductionmentioning
confidence: 99%
“…Sunitinib, a US Food and Drug Administration- (FDA-) approved PDGFR inhibitor, is currently used in the treatment of advanced renal cell carcinoma [37], advanced progressive pancreatic neuroendocrine tumor [38], and advanced radioiodine refractory thyroid carcinoma [39]. Furthermore, ongoing preclinical trials are testing the therapeutic effect of another PDGFR inhibitor, imatinib mesylate, in gastrointestinal stromal tumor [40, 41] and in vitro and in vivo studies of malignant peripheral nerve sheath tumors have shown promising results [42]. Therefore, inhibition of PDGFR in PT might be a potential therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%